The Effect of Circulating Exosomes Obtained from Young and Old Individuals on the Aging related hTERT and P16 Expression in Hematopoietic Stem Cells - Farrokhi, Vida; Afrisham, Reza; Soleimani, Masoud; Ahmadvand, Mohammad; Mousavi, Seyed H.; Kashanikhatib, Zahra; Owchi, Somayeh; Mohammadali, Fatemeh; Alizadeh, Shaban (Natural Products Journal, The, 2024)
Introduction: Functional reduction of telomeres can induce DNA damage response through cell cycle checkpoints and contribute to the senescence of stem cells. The effect of exosomes on the aging and rejuvenation of hematopoietic stem cells (HSCs) is not well known. Therefore, the present study is designed to examine the impact of plasma exosomes derived from young and old individuals on hTERT and P16 expression involved in the cellular aging process. Methods: Exosomes isolated from four young (Y-Exo) and four old (O-Exo) men were evaluated for CD63 protein expression, morphology, size and zeta potential. HSCs were treated with exosomes, and then, the cell viability and the mRNA expression (hTERT and P16) were evaluated using MTT and qRT-PCR methods, respectively. To measure the hTERT protein level, a western blot technique was performed. Results: The gene expression of hTERT was significantly decreased in HSCs treated with 5 μg/ml (O5-Exo) and 10 μg/ml (O10-Exo) doses of exosomes obtained from elderly individuals compared to the cells treated with young exosomes and the untreated HSCs (p < 0.05). In addition, there was a profound elevation of hTERT protein in the HSCs treated with both doses of young exosomes in comparison with the cells treated with both doses of old exosomes (p < 0.05). Moreover, P16 expression was markedly upregulated in the O5-Exo and O10-Exo groups compared to the untreated group (p < 0.05). Conclusion: Our findings reinforce the concept that depending on the age of individuals, circulating exosomes may acquire properties that affect the pathways involved in the aging process in HSCs.
Keywords: hematopoietic stem cells